ChemInform Abstract: Highly Selective Intramolecular Addition of C—N and S—N Bonds to Alkynes Catalyzed by Palladium: A Practical Access to Two Distinct Functional Indoles. Issue 50 (November 2016) - Wu, Chenglin; Zhao, Fei; Du, Yonglei; Zhao, Liang; Chen, Liang; Wang, Jiang; Liu, Hong
Abstract: Two distinct series of functional indoles are prepared by the title addition from the same set of substrates in a catalyst‐controlled manner.